Telegram from Leona Egeland to Jane Tolmach - Leona Egeland:::::: (1976)
This June 10, 1976 telegram from Leona Egeland congratulates Jane Tolmach on her primary victory. Egeland expressed enthusiasm about the prospect of more women serving in the State Legislature and using their talents and influence. She noted that the women's caucus looked forward to welcoming Tolmach into its ranks.